Proposta de um framework para suporte às tomadas de decisões gerenciais sob a ótica da controladoria - Nicolodi, Jamile Zanatta (Universidade do Vale do Rio dos Sinos, 2024)
The presente paper discusses the management decision-making process from the perspective of the Controllership and with an emphasis on economic and financial results. In addition, it is dedicated to a theoretical analysis of the GECON and TOC management models, seeking to integrate them in a timely manner in the context of the organization under study and the Controllership. The objective of this paper is to present a framework that can be configured as a possible solution to be implemented by the organization in order to obtain more effective managers and, consequently, better decision-makers. The framework presents all the informational and relational chains for the success of the proposal. Artificial Intelligence is cited as a decisive potential for the agility of the data-based decision-making process. The development structure was built based on the Design Science Research method and was applied in Strategic Business Unit 1 of the company under study, which also has 3 other strategic units in Rio Grande do Sul. After the construction of the theoretical artifact, it was presented and discussed with 7 managers of the organization, in order to verify its applicability. The framework was then discussed in a focus group with 6 experts from the field, external to the organization, in order to evaluate it and verify the necessary adjustments. The points generated were considered in full or in part in the creation of a new artifact, presented as the final framework to support management decisions focused on economic results.
Keywords: Controladoria; Tomada de decisão; GECON; TOC; Sistemas de informações; Controllership; Decision making; Information systems; ACCNPQ::Engenharias::Engenharia de Produção